Sistem Penyediaan Air Minum di Desa Wedoro, Kabupaten Bojonegoro - Hapsari, Drestanala; Cesaria Wahyu Lukita; Praditya S.Ardisty Sitogasa (Jurnal Serambi Engineering, 2025)
The Drinking Water Supply System (SPAM) is a vital infrastructure in order to fulfill the need for water suitable for consumption for the community, especially in rural areas such as Wedoro Village, Bojonegoro Regency. The results of the study show that the clean water needs of the Wedoro Village community continue to increase along with population growth and regional development. The Bojonegoro District Government responded to this need by building a water treatment plant (WTP) sourced from the Gongseng Reservoir, as well as a clean water distribution network to residents' homes. The SPAM development was carried out in stages involving the construction of intakes, transmission network pipes, distribution pipes, additional pumping units and packages of water treatment plant (IPA) units to increase production capacity, chemical houses, pump houses, and office buildings. SPAM development also went through the process of making Detail Engineering Design (DED) to detail the IPA construction plan. With a large water storage capacity from the Gongseng Reservoir, the SPAM is expected to be able to meet the long-term clean water needs of the Wedoro Village community and its surroundings, improve the quality of life, and support sustainable development in the region.